Evaluation of General and Musculoskeletal Health Literacy Disparities in Pediatric Sports Injury Patient and Guardian Populations. Issue 4 (April 2020) - Su, Lisa; Shaw, Kylie; Serpa, Rebecka O.; Grotts, Jonathan; Bowen, Richard; Beck, Jennifer
Abstract : Background: Increased participation of adolescents in organized sports has led to an increase in pediatric sports injury. Limited health literacy puts patients at risk for worse outcomes through decreased compliance. We aim to evaluate the extent of health literacy disparities in pediatric sports medicine populations. Methods: Patients aged 10 to 17 years and their consenting guardians visiting clinic for treatment of a sports-related injury completed a unique questionnaire including self-reported health literacy measures and direct assessment of knowledge regarding care for musculoskeletal injuries. Statistical analysis based on socioeconomic factors and demographics was performed using t tests. Results: A total of 268 patient surveys (14.37±1.94 y) and 251 guardian surveys (43.62±9.08 y) were collected. In self-reported general health literacy scores for guardians, all categories except ethnicity played a statistically significant role, with higher health literacy scores associated with higher education, use of English as the primary language at home, private insurance, and female guardians ( P <0.001, <0.001, <0.001, 0.011). In contrast, age was the only factor affecting scores in the patient population ( P =0.015). Among self-reported musculoskeletal health literacy and directly measured musculoskeletal literacy scores, there were significant differences in groups by age, primary language, and level of education ( P =0.020, 0.003). Conclusions: Significant disparities in general and musculoskeletal health literacy exist within pediatric sports medicine populations, most notably between guardian groups. Improving disparities in health literacy for these populations may best be aimed at guardians, using medical education through verbal/written instruction in multiple languages. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.